Development and Degradation:: The Emergence and Collapse of the Lobster Fishery on Newfoundland’s West Coast, 1856-1924 - Korneski, Kurt (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2012)
Although the cod fishery has most often been central to the many studies of socio- ecological change in Newfoundland during the past 20 years, other species and industries were also significant to the island’s past. This article examines the lobster fishery on the island’s west coast. Its main argument is that while changes in the cod fishery were important for the lobster fishery in this part of the island, the industry was intimately linked with and shaped by the nature of lobsters themselves, by alterations in local and regional ecological circumstances, and by the changing nature of a northeastern North American regional economy.